The Relationship Between Family Support and Motivation for Cataract Surgery in Older Adults at the Ophthalmology Clinic - Audita Gresti Agasi; Nur Melliza (Discover Health and Medicine, 2025)
Introduction: Cataracts remain the leading cause of visual impairment and blindness among older adults in Indonesia. Family support plays a critical role in motivating elderly patients to undergo cataract surgery. This study aimed to examine the relationship between family support and motivation for cataract surgery among older adults at the Ophthalmology Clinic of Universitas Muhammadiyah Malang Hospital (RSU UMM). Methods: A descriptive correlational design with a cross-sectional approach was employed. The study population consisted of cataract patients aged ≥60 years, selected using purposive sampling, with a total of 40 respondents. Data on family support and motivation were collected using validated questionnaires and analyzed using Spearman’s rank correlation. Results: The results showed that 97.5% of respondents received high family support, and 92.5% exhibited high motivation to undergo surgery. Spearman correlation analysis revealed a significant positive correlation between family support and motivation for cataract surgery (r = 0.562, p < 0.001). Conclusion: These findings suggest that higher family support is associated with increased motivation for cataract surgery in older adults. Nursing and healthcare interventions should involve family members to enhance patient motivation and ensure successful surgical outcomes.